Cellular Signaling in Müller Glia: Progenitor Cells for Regenerative and Neuroprotective Responses in Pharmacological Models of Retinal Degeneration - Yang Liu; Chenguang Wang; Guanfang Su (Journal of Ophthalmology)
Retinal degenerative diseases are a leading cause of visual impairment or blindness. There are many therapies for delaying the progression of vision loss but no curative strategies currently. Stimulating intrinsic neuronal regeneration is a potential approach to therapy in retinal degenerative diseases. In contrast to stem cells, as embryonic/pluripotent stem cell-derived retinal progenitor cell or mesenchymal stem cells, Müller glia provided an endogenous cellular source for regenerative therapy in the retina. Müller glia are a major component of the retina and considerable evidence suggested these cells can be induced to produce the lost neurons in several species. Understanding the specific characteristic of Müller glia to generate lost neurons will inspire an attractive and alternative therapeutic strategy for treating visual impairment with regenerative research. This review briefly provides the different signal transduction mechanisms which are underlying Müller cell-mediated neuroprotection and neuron regeneration and discusses recent advances about regeneration from Müller glia-derived progenitors.